PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII MTsN 4 KOTA PALU: Application Of STAD Tipe Cooperative Learning Model To Increase Student Results Class VII MTsN 4 Kota Palu - Nggariwo, Febryanti; M., Bakri; Hadjar, Ibnu; Rochaminah, Sutji; Hatin, Murni A. (Aksioma, 2024)
This research aims to describe the application of the STAD type cooperative learning model that can improve student learning outcomes on line and angle material at MTs Negeri 4 Palu City. This research is a Classroom Action Research (PTK) with Kemmis and Mc. Taggart design. This research was conducted in two cycles with 20 students, with two meetings in each cycle that followed the steps of the STAD type cooperative learning model. The results of the study: (1) the results of teacher activity observations in cycle I reached 79.41% with good criteria and in cycle II reached 94.11% with very good criteria. While the observation of student activities in cycle I reached 73.52% with good criteria and in cycle II reached 85.29% with very good criteria. (2) the percentage of classical learning completeness in cycle I was 55% and cycle II reached 75% Thus it can be concluded that there is an increase in student learning outcomes on line and angle material in class VIIe MTs Negeri 4 Palu City by applying the following phases: (1) class presentation, (2) transition to team/group learning, (3) team study and monitoring, (4) evaluation/test, (5) awarding.